Risks for the Long Run and the Real Exchange Rate - Colacito, Riccardo; Croce, Mariano M. (Journal of Political Economy, 2011)
We propose an equilibrium model that can explain a wide range of international finance puzzles, including the high correlation of international stock markets, despite the lack of correlation of fundamentals. We conduct an empirical analysis of our model, which combines cross-country-correlated long-run risk with Epstein and Zin preferences, using U.S. and U.K. data, and show that it successfully reconciles international prices and quantities, thereby solving the international equity premium puzzle. These results provide evidence suggesting a link between common long-run growth perspectives and exchange rate movements.